2006
DOI: 10.1137/050628362
|View full text |Cite
|
Sign up to set email alerts
|

Structured Polynomial Eigenvalue Problems: Good Vibrations from Good Linearizations

Abstract: Many applications give rise to nonlinear eigenvalue problems with an underlying structured matrix polynomial. In this paper several useful classes of structured polynomials (e.g., palindromic, even, odd) are identified and the relationships between them explored. A special class of linearizations which reflect the structure of these polynomials, and therefore preserve symmetries in their spectra, is introduced and investigated. We analyze the existence and uniqueness of such linearizations and show how they ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
323
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 251 publications
(327 citation statements)
references
References 16 publications
2
323
0
2
Order By: Relevance
“…which, as in the palindromic case detailed before, can be used mutatis mutandis to construct an alternating linearization for P. Similar results were proved for the other flavors of palindromicity and alternation, and concrete examples given in [56].…”
Section: In Ansatz Spacessupporting
confidence: 50%
See 4 more Smart Citations
“…which, as in the palindromic case detailed before, can be used mutatis mutandis to construct an alternating linearization for P. Similar results were proved for the other flavors of palindromicity and alternation, and concrete examples given in [56].…”
Section: In Ansatz Spacessupporting
confidence: 50%
“…This Cayley transformation was extended from matrices to matrix pencils in [50], and in a 1996 paper by Mehrmann [67]. It was then generalized to matrix polynomials in 2006 by Mehrmann and co-authors [56], where it was shown how palindromic and alternating structures are related via a Cayley transformation of matrix polynomials. The definition of general Möbius transformations in [61] completes this development, providing an important and flexible tool for working with matrix polynomials.…”
Section: Möbius Transformationsmentioning
confidence: 99%
See 3 more Smart Citations